2018
DOI: 10.20944/preprints201809.0283.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Detection of Periodic Radio Signal from the Blazar J1043+2408

Abstract: Search for periodic signals from blazars has become widely discussed topic in recent years. In the scenario that such periodic changes originate from the innermost regions of blazars, the signals bear imprints of the processes occurring near the central engine, which is mostly inaccessible to our direct view. Such signals provide insights into various aspect of blazar studies including disk-jet connection, magnetic field configuration and, more importantly, strong gravity near the supermassive black holes and … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 45 publications
(59 reference statements)
0
4
0
Order By: Relevance
“…The precession of a slowly rotating black hole with a high mass accretion rate and a low α vis (as confirmed by observations [49]) can occur with the found period. On the other hand, it is possible that misalignment of the black hole and accretion disc rotation axes can cause precession of the outer part of the accretion disc with a period [48]:…”
Section: Helical Jet Precessionmentioning
confidence: 99%
“…The precession of a slowly rotating black hole with a high mass accretion rate and a low α vis (as confirmed by observations [49]) can occur with the found period. On the other hand, it is possible that misalignment of the black hole and accretion disc rotation axes can cause precession of the outer part of the accretion disc with a period [48]:…”
Section: Helical Jet Precessionmentioning
confidence: 99%
“…As a result, the hunt for periodic signals in blazar light curves has become an active field of research: blazar OJ 287 is famous for its ∼12-year periodicity detected in its historical optical light curve [6,7] and another famous source PG 1553 + 113 is found to show 2.18-year periodic modulations in its γ-ray observations from the Fermi/LAT, which was first reported in [8]. In addition, several authors have reported the existence of QPOs of various characteristic timescales in numerous blazar multi-frequency light curves including the four cases of QPO detection by our research group see [4,[9][10][11] and the references therein.…”
Section: Introductionmentioning
confidence: 54%
“…As an illustration, for blazars having typical radio spectral index (α = 0.6) and viewing angles in the 1-5 • range, a slight change in the viewing angle e.g., ∼1.5 • , is sufficient to produce observed maxima twice as bright as minima in the light curves refer to Figure 4 in [10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation